Incidence of psychological burnout in medical students from a private university in Lima during an academic semester in 2023 - Yan Cedrón, Jorge (2024)
Psychological burnout or Burnout Syndrome (SBO) is a widely studied phenomenon that particularly affects younger populations; however, in our country, there are no longitudinal reports on its presence among medical students. Objective: To determine the incidence of Burnout Syndrome (SBO) in medical students over the course of an academic semester in 2023, and to explore closely associated factors. Materials and methods: An observational, longitudinal study was conducted using a panel design. The dimensions of Burnout Syndrome (SBO) were measured with the Maslach Burnout Inventory - Student Survey (MBI-SS) at three different periods during the academic semester, along with other related variables. Bivariate tests for comparing proportions at different points in time were applied; the determination of factors associated with incidence was carried out using a generalized estimating equations (GEE) model with a binomial family. Results: The presence of SBO was 5.7%, 12.5%, and 19.3% in the first, second, and third periods, respectively. The cumulative incidence of SBO from T1 to T2 was 11.4%, from T2 to T3 was 12.5%, and for the entire follow-up, 29.6%. The presence of SBO increased among those born in provinces, living with four or more people, and not commuting exclusively on foot. Conclusion: The presence of SBO significantly increases throughout the academic semester and affects men more. Factors such as academic activities increase the risk of SBO in upper-year students and among those without religious affiliation.